Virgens, vadias, assassinas, loucas, lúcidas, mães...um estudo sobre o ethos da mulher em filmes de horror hollywodianos - Cavalcante, Derick Rafael Santos (2023)
Being aware about role and prominence of female characters in the horror cinematographic genre, this dissertation proposes to analyze how the discursive images – the ethos – of seven of these characters in five Hollywood films of the 20th and 21st centuries are constructed. As specific objectives, we propose: i) to investigate how the relation between fiction and social reality occurs in the representation of women in the cinematographic universe of the genre; ii) to reflect on how the various resources present in the cinematographic language crystallize discourses and stereotypes in their works; iii) to identify verbal and non-verbal strategies used in horror films in the construction of the discursive image of the female character. For this, among others, the research appropriates concepts from the studies of neo-rhetorics and discursive argumentation, such as audience (PERELMAN; OLBRECHTS-TYTECA, 2005), ethos, stereotypes and clichés (ARISTÓTELES, 2005; AMOSSY, 2016, 2022; MAINGUENEAU, 2020). In addition, the ethos trap concept (CAVALCANTE, 2023) helps to identify some images in our objects of analysis. Furthermore, it presents the horror cinematographic genre, through Clover (1992) and Carroll (1990); reflects on the history of women's place in society, from Rubin (1975) and Butler (1990) and seeks to understand how non-verbal resources make up the cinematographic language, through Santana (2022). The research methodology is based, above all, on screen ethnography (RIAL, 2004), with the analysis of the verbal and non-verbal text, such as costumes and lighting, and external agents (production, direction, etc.). As results, diversified and plural (sometimes contradictory) female ethos are revealed. Strong and resilient ethos of women who overcome their obstacles and prevail as winners/heroines throughout the projection; murderous and monstrous ethos that are often constructed as helpless for the audience during the narrative; ethos of madmen and sinners, among others. At the same time, there has been a change in the construction of the discursive image of female characters in horror productions over the years, reducing the appearance of negative and stereotyped ethos, due to the new airs and equally plural faces that horror productions are assuming in addition to studies that directly influence the evolution of the genre.